ANALISIS KESESUAIAN PENGGUNAAN BUKU METODE RINGKAS TERPADU DALAM IMPLEMENTASI KURIKULUM MERDEKA PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS 3 MIN 2 BANDA ACEH - Ulfia, Khaira; Isa, Muhammad; Aswita, Dian (Jurnal Seramoe Education, 2025)
This study aims to analyze the suitability of the use of the Integrated Compact Method book in Indonesian subjects. The approach in this study is qualitative. The type of research used is qualitative descriptive. This research was conducted at MIN 2 Banda Aceh. The object of this study is the book Integrated Compact Method (MRT). Data collection techniques are in the form of analysis and documentation.The data analysis techniques in this study are data reduction, data presentation, and conclusion drawn. The results of the study show that the Integrated Compact Method book is in accordance with the indicators of the textbook in general such as the completeness of the material, the breadth of the material, the depth of the material, the accuracy of the procedure, the fact of the sample content and questions, the up-to-date features of the examples and references, reasoning, application are also the attractiveness of the material. Thus, the final conclusion reached is that the Integrated Compact Method (MRT) book is suitable for use as a textbook, but teachers who use the book as a textbook must have other teaching guidelines.